Carbon accumulated in roots of plant species in silvopastoral systems in northern Colombia - Contreras-Santos, José Luis (2021)
[Introduction]: Silvopastoral systems (SPSs) are sustainable alternatives to manage soils dedicated to livestock production, contributing to the recovery of degraded soils. [Objective]: Know the potential of carbon capture (C-capture) in fine root biomass per species and their exploration capacity in the soil between two SPSs (A1 - Megathyrsus maximum cv Mombasa associated with the shrub species, Leucaena leucocephala and Crescentia cujete; A2 - combination of A1 + tree species, Guazuma ulmifolia, Cassia grandis, and Albizia saman) and meadows without trees (A0 - M. maximum cv Mombasa), in the middle valley of the Sinú River. [Methodology]: A randomized complete block design was used with three treatments and three repetitions, in which fine root biomass (FRB, ≤ 5 mm) was determined with a cylinder of known volume and root length density (RLD) using a flatbed scanner; physicochemical properties of soil were also determined. [Results]: L. leucocephala showed high values of C accumulation in root biomass (441.5 kg C ha-1) compared to the other species evaluated. In contrast, C accumulated in grass roots was affected by the SPS complexity, reducing 59 % (A1) and 34 % (A2), with respect to A0. The highest RLD was recorded in the C. cujete and L. leucocephala species (249.7 ± 199.5 and 239.3 ± 135.02 cm cm-2, respectively). [Conclusions]: SPSs accumulate higher C in root biomass and improve the soil’s physicochemical properties.